From Village to Virtual Education: Advancing Literacy Through Innovation at SDN Sumberjati - Iman Subekti; Gunawan Tanuwidjaja; Michael Kurniawan; Efraim Jason Indargo (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2026)
This community engagement program was carried out with the aim of strengthening early literacy competency among elementary teachers and students in rural areas. It focused on SDN Sumberjati, where students and teachers still have limited access to learning materials, proper technology, and only a little exposure to digital literacy. The program tried to introduce a kind of hybrid learning idea called From Village to Virtual Education, combining literacy mentoring, use of simple digital classroom platforms, and creative learning activities adjusted to the rural situation. The implementation involved university volunteers working closely with the school, including students, teachers, and the school administrators. The process moved through four main stages, which were needs assessment, planning with capacity building, running the literacy activities, and then evaluation. The results showed a clear improvement in students' reading interest, their willingness to join digital learning sessions, and their ability to express ideas in more creative ways. The teachers also gained practical experience in using digital tools and trying literacy enrichment practices in their classrooms. The community around the school received social and economic benefits as well because collaboration between the school and parents became stronger, and some basic digital learning facilities started to be maintained in a more sustainable way. This program shows that these kinds of educational efforts can really help in reducing the learning gaps that still happen in many rural communities, and it gives students a chance to reach digital learning in a more equal way. For the future plan, the team plans to keep mentoring, propose open-source learning materials, and also expand the program to other schools in the region.